Effects of Structural Changes in Cross-Linked Mung Bean Starch on Freeze–Thaw Properties and In Vitro Digestibility - Altantungalag Agvaandorj; Yuanzao Li; Junhee No (Foods)
This study aims to evaluate the effects of structural changes in cross-linked mung bean starch (CLMB) on freeze–thaw stability and in vitro digestibility and explore its potential to prevent starch retrogradation and its applicability as a resistant starch (RS)- enhanced food ingredient. Mung beans of different varieties (Eohul, Geumsung, and Sohyeon) were cross-linked using an STMP:STPP ratio of 9:1. The structure and thermal properties of CLMB and its digestibility, as well as the textural properties of 10% CLMB gels and their freeze–thaw stability, were evaluated. As a result of the study, CLMB maintained an A-type crystalline structure, but structural changes due to the introduction of phosphate groups were observed during FT-IR analysis. Compared to natural mung bean starch (MBS), the swelling power and solubility decreased, and the gelatinization temperature range increased. Additionally, the cross-linking treatment increased the resistant starch (RS) content. In the case of the gel with 10% CLMB added, the freezing–thawing experiment results show a significant reduction in syneresis and it was confirmed that high stability was maintained even through repeated processes. Our results suggest that CLMB is a functional ingredient with potential applications in the development of food products offering extended shelf lives and tailored nutritional benefits.